Consolidation and permeability behaviour of Newark Bay's dredged sediments by seepage-induced consolidation test. Issue 2 (15th March 2017) - Janbaz, Masoud; Maher, Ali
Abstract : Annually, two to four million cubic yards of sediments need to be dredged to maintain the navigational depth for cargo ships in NY/NJ harbours. The dredged sediments are hydraulically disposed into impoundment ponds and capped. The limitations on disposal sites force the designer to design the ponds to its fullest capacity which requires understanding of consolidation behaviour of these sediments. Dredged sediments, however, do not follow the traditional consolidation behaviour proposed by Terzaghi. The limitations and simplifying assumptions of infinitesimal strain and constant permeability make the traditional consolidation theory impractical dealing with these sediments. Therefore, a consolidation apparatus based on seepage force was constructed in Rutgers University to account for all of the shortcomings of traditional consolidation. The outcome of this research programme showed that this method of testing is applicable to the soft sediment consolidation testing and provides reliable and repeatable results.